Water quality assessment of Nwangele river in Imo State, Nigeria - Joseph, Anudike; Majesty, Duru; Friday, Uhegbu (Journal of Ecobiotechnology, 2019)
Water quality assessment of Nwangele river was undertaken using standard methods. Water samples were drawn from upstream, midstream and downstream of the river and assessed for quality. Results obtained for physicochemical characteristics showed pH (4.83±.0.01-5.00±0.31), total solid (200.00±2.40-613.19±1.10 mg/L), and total suspended solid (49.98±0.11-399.04±2.09 mg/L). Heavy metals found in the river water were iron (0.132±0.01- 0.144±0.02 mg/L), zinc (0.034±0.02- 0.044±0.02 mg/L), mercury (0.004±0.001- 0.011±0.00 mg/L), lead (0.008±0.00- 0.016±0.00 mg/L) and cadmium (0.03±0.01- 0.011±0.00 mg/L). Microbiological studies on the river revealed the presence of Klebsieilla sp., Vibro sp., Pseudomonas sp., Proteus sp., Escherichia sp., Staphylococcus sp., Shigella sp., Bacillus sp., Serratia sp., Citrobacter sp., and Enterobacter sp as bacterial isolates with high total heterotrophic bacteria count (THBC), total coliform count (TCC), Salmonella-shigella count (SSC), and total viable count (TVC). Nwangele River water is acidic, with high total suspended solid, phosphate and microbial loads. It is therefore advisable to purify water from the river before consumption. This study has assessed the water quality of Nwangele river in Imo State, Nigeria